Unveiling vegetation recovery dynamics in Andean grasslands along a trans-Andean natural gas pipeline - Fiorella Eduardo-Palomino; Héctor Chuquillanqui; Reynaldo Linares-Palomino (Ecological Indicators)
To unveil the temporal vegetation recovery dynamics in the Andean grasslands, we propose a new index that incorporates species abundances, data variation, and a continuously updated control mean. To test whether this index can identify areas with varying recovery rates, we used data collected yearly by a restoration monitoring program over nine years (2010–2019, except 2017). This data was gathered along a trans-Andean gas pipeline right-of-way, encompassing 276 km of restored Andean grasslands of the Ayacucho and Huancavelica regions in southern Peru. The study area was divided into 12 large ecological landscape units (ELUs) to facilitate data comparison and interpretation. All 12 ELUs were further divided into 500 m sections and evaluated by placing a pair of 100-meter transects (within and outside of the right-of-way) within each section. Field-collected data were standardized and meticulously cleaned to ensure accuracy and consistency over time. Statistical analyses were conducted, and vegetation recovery was visualized at different spatial and temporal scales. The results revealed general trends of vegetation recovery at the ELU level, with a majority displaying a positive recovery trajectory. The new index, which incorporates species abundance and a control mean, offers a comprehensive and precise measure for understanding the temporal and spatial aspects of grassland restoration. Nevertheless, the study acknowledges certain limitations and challenges, such as the necessity for long-term data and the consideration of other environmental and management factors that can impact vegetation recovery. Ultimately, the new index presents itself as a valuable tool for assessing and monitoring the effectiveness of restoration activities in areas of Andean grasslands affected by development projects.